2014
DOI: 10.1021/jp501709q
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Adsorption Coverage Study on Platinum and Ruthenium Surfaces

Abstract: Periodic density functional theory calculations elucidate carbon monoxide coverage effects on platinum and ruthenium surfaces. As expected the CO stretching frequencies increase with coverage. Unexpectedly, overlap population calculations show that increased stretching frequencies may not always correspond to stronger bonds. A theoretical framework is established based on a modified π-attraction σ-repulsion scheme. This phenomenological model directly relates the internal adsorbate bond strength to the net cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 78 publications
0
30
1
Order By: Relevance
“…McEwen et al, 25 computed two CO adsorption models on Ru(0001); the first one with CO adsorbed upright on top and hollow sites and the second one with CO adsorbed tilted on top sites; and found that the second model is more consistent with the experiment on the basis of the IR results. 26 In contrast to CO, H 2 adsorption is dissociative on Ru(0001) and the saturation fractional coverage is one adatom per Ru(0001) unit cell. 26 In contrast to CO, H 2 adsorption is dissociative on Ru(0001) and the saturation fractional coverage is one adatom per Ru(0001) unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…McEwen et al, 25 computed two CO adsorption models on Ru(0001); the first one with CO adsorbed upright on top and hollow sites and the second one with CO adsorbed tilted on top sites; and found that the second model is more consistent with the experiment on the basis of the IR results. 26 In contrast to CO, H 2 adsorption is dissociative on Ru(0001) and the saturation fractional coverage is one adatom per Ru(0001) unit cell. 26 In contrast to CO, H 2 adsorption is dissociative on Ru(0001) and the saturation fractional coverage is one adatom per Ru(0001) unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the electronic effect and bifunctional mechanism both effectively work to inhibit the CO ads poisoning in MOR. In terms of the Pt/TiO 2 @NC X -900 catalyst, the nitrogen doping in carbon framework will strengthen the interaction between TiO 2 @NC X -900 and Pt NPs, modify the electronic structure of the supported Pt, leading to a lower density of states at the Fermi level, thus reduce the PteCO band energy and weaken the CO adsorption on the Pt surface [29,30]. This modified electronic structure of Pt induced by the specific metalesupport interactions may be responsible for the enhanced activity for MOR.…”
Section: Samplesmentioning
confidence: 99%
“…[9,10] In the Blyholder model bonding is attributed to electron transfer from the occupied 5σ molecular orbital (MO) of CO to the empty Pt d-states and back-donation of electrons from occupied Pt dstates to the CO 2π* MO, which is unoccupied in the free CO molecule. The hybridized level between the empty Pt d-states and the 2π* MO of CO is antibonding in C-O, but bonding in Pt-C. [11] Despite the extensive efforts of previous research, it remains challenging to experimentally probe the influence of the charge at the reactive site and of binding site coordination on the CO adsorption energy. This is a direct consequence of the difficulty to measure and control parameters such as the reactive site's charge state and coordination number.…”
Section: Introductionmentioning
confidence: 99%